Prevalence of Chronic Kidney Disease (CKD) in Newly Diagnosed Heart Failure Patients, its Correlation with Disease Severity and the Requirement for High-Dose Loop Diuretics - Sohail Ahmed, Adnan Qaiser, Shahidah Zaman, Irfan Ahmad, Basma Shakeel, Ali Saqlain Haider (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Heart failure often coexists with impaired renal function, yet the prevalence ofchronic kidney disease (CKD) at the time of initial heart failure diagnosis and its relationship with disease severity remains under-explored.